2005
DOI: 10.1254/jphs.fp0050300
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Inducible Nitric Oxide Synthase Attenuates Renal Ischemia and Damage in Experimental Heatstroke

Abstract: Abstract. The aim of the present study was to determine whether the possible occurrence of renal ischemia and damage during heatstroke can be suppressed by prior administration of L-N6-(1-iminoethyl) lysine (L-NIL), a selective inducible nitric oxide synthase (iNOS) inhibitor. Urethane-anesthetized rats were exposed to heat stress (43°C) to induce heatstroke. Control rats were exposed to 24°C. Mean arterial pressure and renal blood flow after the onset of heatstroke both were significantly lower in vehicle-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Our results further showed that pretreatment with aminoguanidine, an inhibitor of inducible nitric oxide synthase (iNOS), significantly reduced the heat stroke‐induced hyperthermia, arterial hypotension, intracranial hypertension, cerebral ischaemia and increased iNOS‐dependent NO formation in the brain 77 . l ‐ N 6‐(1‐Iminoethyl) lysine ( l ‐NIL), a relatively selective iNOS inhibitor, 78,79 has also been shown to protect against renal ischaemia and damage during heat stroke by reducing hyperthermia and arterial hypotension in rats 80 …”
Section: Inducible Nitric Oxide Synthase Inhibitors Protect Against Hmentioning
confidence: 99%
“…Our results further showed that pretreatment with aminoguanidine, an inhibitor of inducible nitric oxide synthase (iNOS), significantly reduced the heat stroke‐induced hyperthermia, arterial hypotension, intracranial hypertension, cerebral ischaemia and increased iNOS‐dependent NO formation in the brain 77 . l ‐ N 6‐(1‐Iminoethyl) lysine ( l ‐NIL), a relatively selective iNOS inhibitor, 78,79 has also been shown to protect against renal ischaemia and damage during heat stroke by reducing hyperthermia and arterial hypotension in rats 80 …”
Section: Inducible Nitric Oxide Synthase Inhibitors Protect Against Hmentioning
confidence: 99%
“…2008.03.001 in adaptive responses of an organism to stress conditions. NO production may be altered by a variety of stressors including restraint (Masood et al, 2004), immobilization (Shirakawa et al, 2004), hypoxia (Manukhina et al, 2000), hypo-and hyperthermia (Han et al, 2002;Lee et al, 2005), pain shock (Aley et al, 1998), and physical training (Green et al, 2004; see also a review by Malyshev and Manukhina, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although hyperthermia in the range of heat shock (43°C) can directly induce NO synthase and cause systemic hypotension and death in a rat model of heat stroke, our model of fever-range hyperthermia did not independently affect plasma concentration of NO metabolites (23,41). This study does not address whether the increased NO concentration observed in the mice exposed to hyperthermia and LPS was attributable to direct induction of NO synthase or the effect of increased production of inflammatory cytokines in the peripheral blood leukocytes.…”
Section: Discussionmentioning
confidence: 71%